A Qualitative Analysis of Physically Aggressive Conflict Episodes Among a Community Sample. Issue 21 (November 2020) - Testa, Maria; Petrocelli, Laura T.; Crane, Cory A.; Kubiak, Audrey; Leonard, Kenneth E.
Intimate partner aggression among community couples has been conceptualized as representing an occasional, situationally provoked response to a conflict. Yet, relatively few studies have considered the situational factors that contribute to the occurrence of an aggressive episode. The present study used thematic analysis to understand how episodes of physical aggression come about from the participant's perspective. We examined narrative descriptions of relationship conflicts that included physical aggression to gain insight into the types of aggressive incidents experienced, the reasons and motives behind the aggression, and the meaning of these events. Married and cohabiting couples (ages 18-45 at baseline) were recruited from the community to participate in a longitudinal study of relationships. Heavy drinking couples were oversampled. At Wave 3, participants were asked to describe the most severe conflict they had experienced over the past year and to answer questions about severity and impact. Narratives that described use of partner physical aggression by one or both partners were subject to thematic analysis. Using narratives provided by 27 male and 29 female respondents (representing 51 different couples), we identified three primary motives or reasons for aggression: Expressive, Instrumental, and Punishment. Narratives suggested as a primary theme that participants view partner violence as unusual, undesirable, and hence, meaningful. This was particularly true for male-to-female violence, which appeared objectively and subjectively different from female-to-male violence. Findings provide unique insight into the function and meaning of partner violence, including its gendered nature, within a community sample. Implications for measurement of partner aggression are also discussed.